Investigation On Water Softening Using Surfactant Modified Bentonite Adsorbent Coating - Ab Kadir, Nur Nadia (2017)
Adsorbent coating of bentonite modified (SMB) sodium dodecylbenzene sulfonate surfactant (SDBS) has been developed for the removal of Ca2+ and Mg2+ ions from hard water. The adsorbent was characterized using SEM, EDX, Zeta-meter and FTIR analyses. It has potential to replace the expensive conventional softening treatment techniques as well as reduce the usage of excess chemicals (chemical precipitation) by applying onto treatment area. Formulation of SMB was carried out including evaluation effect of surfactant ratio, effect of different type of binder and effect of adsorbent to binder ratio with best formulation by using PVAc binder, with adsorbent to binder ratio 0.75:1.0 ratio (w/w). The optimum condition of softening hard water was obtained with highest removal efficiency 66.6% (29.27mg/g) using 120 mg/L hard water, 300 rpm mixing speed, pH 6.8, and 30°C. SMB adsorbent coating can be reused for two times only. The separate calcium and magnesium solution were conducted and magnesium is preferable than calcium due to the availability active sites between magnesium and anionic functional group of SMB surface. The adsorption in this study was fitted with Langmuir isotherm and pseudo-second order model. Thermodynamic parameters (ΔH°, ΔS°, and ΔG°) revealed exothermic nature and reaction is spontaneous. In desorption study, 0.1M H2SO4 provide the highest desorption and adsorption/desorption cycle achieved up to third cycle. On the basis of good removal capacity towards Ca2+ and Mg2+ ions, SMB adsorbent coating can be effectively used for softening of hard water.